Determinan Pengetahuan Ibu Terhadap Ketepatan Pemilihan KB Suntik 3 Bulan (Depo Progestin) Di Wilayah Kerja Puskesmas Pringapus - Nabilla Qoni Maharani; Kristina Maharani; Siti Juwariyah (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Introduction: 3-month injection KB (Depo Progestin) is a contraceptive method that can be used effectively and has good working power for mothers. The use of 3-month injectable birth control aims to delay or prevent pregnancy, space pregnancies, and terminate pregnancies. Mother's knowledge plays an important role in choosing birth control; the more knowledge the mother has, the more influential she is in choosing injectable contraceptives. Based on Indonesia's profile data in 2019, there was an increase in contraceptive use in women, namely 50% to 64% in the 1991–2017 period, but in 2019 it decreased to 62.5%. The most dominant contraceptive method used in 2019 was the injection contraceptive method as much as 63.7% (Central Statistics Agency data) and based on health profile data for Central Java province in 2021, there is an increase in the use of injectable birth control among married women aged 15–49 years, namely 57.68%. Objective: This study aims to determine the determinants of mother's knowledge on the accuracy of choosing 3-month injectable birth control (Progestin Depo) in the working area of ​​the Pringapus Health Center. Metodes: This research method uses a cross-sectional research method and a purposive sampling approach. The sample used in this study was 92 respondents, and the location of this research was in the working area of the Pringapus Health. Results: Based on data analysis the result is that mothers with good knowledge are 53 (57.7%) respondents, and the accuracy in choosing the answer